Recreation of personal identity from a complex and holistic approach - Ávalos Rodríguez, Ileana (2018)
The search for meaning for people has been presented throughout history as the most challenging tasks on a personal level. The article offers a look to recreate personal identity from a self empowerment that starts from a direct and symbiotic relationship with subjectivity, alterity, the ancestral and spirituality. To achieve this, the subjectification action is taken as a starting point. Subsequently, conceptual elements are offered to approach alterity from a complex and holistic perspective. Later, the offered theory is discussed with some spiritual practices that are based on the construction of the personal identity from the collective identity.